Effectiveness of crystallization test in screening of potentially malignant oral disorders and oral cancer - Ratna Kumari V N Tarigoppula; B R Ahmed Mujib; Rashmi Naik (Wolters Kluwer Medknow Publications, 2018)
Aim: This study aims to determine the effectiveness of crystallization test in screening of oral potentially malignant disorders (PMDs) and oral cancer. Materials and Methods: Thirty patients of oral PMD, 30 patients of oral cancer and 40 normal healthy people were selected. One drop of blood was collected and added to 1 cc of double-distilled water at room temperature to get a final dilution of 6% hemolyzed blood. 0.1-0.2 cc of this blood sample is added to 10 cc of 20% cupric chloride solution and further is subjected to crystallization test. Results: In the normal healthy group, the pattern was typical with an eccentrically placed center of gravity with needles arranged in radiating fashion. Whereas in oral PMD and cancer groups, there was "transverse form" formation. This test had sensitivity and specificity of about 83.33% and 86.84% for PMDs group and 96.30% and 86.84% for oral cancer group respectively. Conclusion: Crystallization test was found to be sensitive, reliable, economical and less-invasive procedure for screening of oral PMDs and oral cancer.